Butterfly Pea Flower as a Novel Ingredient to Produce Antioxidant-Enriched Yellow Pea-Based Breakfast Cereals - Ravinder Singh; Cheng-Chia Yu; Guan-Wei Chen; Ching-Hsueh Chen; Nasibeh Y. Sinaki; Jenshinn Lin; Filiz Koksel (Foods, 2022)
Butterfly pea flower (BP) is a rich source of bioactive components and can potentially be utilized to produce appealing, wholesome foods. Antioxidant and dietary fiber-enriched breakfast cereals were produced by extrusion cooking using blends of BP and yellow pea flour (YP). BP was added to YP at 0%, 5% and 10% levels (w/w), respectively, and extruded at two temperature profiles with die temperatures of 130 and 150 °C. Incorporation of BP significantly (p < 0.05) improved the total phenolics content, antioxidant properties, and insoluble and total dietary fiber content of the extrudates, with 10% BP extrudates showing the highest values. At a die temperature of 150 °C, the extrudates had a higher expansion ratio, a lower dry hardness, and a higher dry crispiness as compared to those at 130 °C. The color of BP-incorporated extrudates was darker and bluer as compared to the no-BP extrudates. The 10% BP extrudates retained relatively more of their hardness, crispiness, and crunchiness after soaking, indicating a better bowl-life and, therefore, better suitability of this blend formula for breakfast cereal production. Overall, this research shows that healthier breakfast cereals with appealing color and relatively longer bowl-life can be produced using BP, making BP a potential novel ingredient for extrusion formulations.